A strategy for effective latent HIV reactivation using subtherapeutic drug doses. Issue 1 (December 2017) - Cotterell, James; Neely, G.
Abstract Cell state switches underlie a plethora of biological phenomena and disease treatment strategies. Hence the ability to efficiently switch states in a chosen direction is of central importance in a number of scenarios. Increasing the concentration of an effector that results in a given switch is often limited by side effects. Approaches are thus increasingly sought to bypass these constraints, increasing the frequency of state switching without increasing the frequency of the side effect. Here, we employ dynamical systems theory to uncover a simple strategy as to how to maximize the probability of reactivating latent Human immunodeficiency virus (HIV) whilst maintaining minimal side effects. We demonstrate that continuous supply of an effector is significantly more likely to result in a switch with minimal side effects than the same effector supplied in temporally discrete doses. Importantly this continual dosage is likely to occur far below the Minimum effective dose at a concentration that has classically been thought subtherapeutic. We therefore suggest that in many interventional settings there exists potential to reduce drug dose much further than has previously been thought possible yet still maintaining efficacy.